Principal's Learning Leadership to Developing Student Leadership in Vocational High Schools - Pujihastuti, Asri; Darsinah, D; Wafroturrohmah, W (Proceedings International Conference on Education Innovation and Social Science, 2023)
The principal has an important role as a manager in school management that affects the quality of the school. Learning leadership from a principal is needed to design and implement educational programs. This study aims to describe the implementation of learning leadership by principals in developing student leadership. This research is a type of qualitative research that produces descriptive data and is analyzed in the form of written words from observed individual behavior. The methods used in this research include interviews, observation, and documentation to collect data. The results of the research at SMK Negeri 7 Surakarta show that learning leadership by the principal has an important role in developing student leadership. The principal's efforts in implementing effective learning leadership have improved student leadership through giving voice, choice, and ownership according to expectations that are planned, implemented, and evaluated. SMK Negeri 7 Surakarta also encourages the development of student leadership through the activities of the Intra-School Student Organization (OSIS), extracurricular activities, entrepreneurial spirit development and collaboration with other students and teachers. This helps to increase students' active participation in the implementation of school programs. Internal factors that influence the implementation of learning leadership include school strengths and weaknesses, facilities and infrastructure, teachers, principals, and financing. While external factors include external opportunities and challenges such as government policies, information and communication technology, and cooperation with other parties such as IDUKA. Internal and external factors also influence the implementation of learning leadership.